2020
DOI: 10.3892/etm.2020.8453
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury and its underlying mechanism in rats with temporal lobe epilepsy

Abstract: Numerous cases of spinal cord injury following seizure have been previously reported. However, whether spinal cord injury is a common occurrence after seizures and its underlying mechanisms remain unclear. The present study generated a Sprague-Dawley rat model of temporal lobe epilepsy (TLE), and Nissl staining and transmission electron microscopy were used to detect tissue damage. In addition, Evans blue staining was used to detect damage to the blood-brain barrier (BBB) and albumin extravasation. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Apoptosis of neurocytes was found around the damaged area in the spinal cord of patients who died of SCI in 3 h to 2 months, with degenerative changes occurred in adjacent segments ( Emery et al, 1998 ). Besides, studies have confirmed that neurocytes necrosis was dominant in the early stage of SCI in rats, and the apoptosis of neurocytes began in 6 h after injury, which could last for 2 weeks or even longer ( Liu et al, 2020 ). Panx1 was correlated with the inflammatory response ( Pelegrin and Surprenant, 2006 ; Orellana et al, 2013 ), Pyroptosis ( Kayagaki et al, 2011 , 2013 ; Hagar et al, 2013 ; de Gassart and Martinon, 2015 ; Yang et al, 2015 ), and autophagy ( Ayna et al, 2012 ; Martins et al, 2014 ) after nervous system injury, which promoted apoptosis in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of neurocytes was found around the damaged area in the spinal cord of patients who died of SCI in 3 h to 2 months, with degenerative changes occurred in adjacent segments ( Emery et al, 1998 ). Besides, studies have confirmed that neurocytes necrosis was dominant in the early stage of SCI in rats, and the apoptosis of neurocytes began in 6 h after injury, which could last for 2 weeks or even longer ( Liu et al, 2020 ). Panx1 was correlated with the inflammatory response ( Pelegrin and Surprenant, 2006 ; Orellana et al, 2013 ), Pyroptosis ( Kayagaki et al, 2011 , 2013 ; Hagar et al, 2013 ; de Gassart and Martinon, 2015 ; Yang et al, 2015 ), and autophagy ( Ayna et al, 2012 ; Martins et al, 2014 ) after nervous system injury, which promoted apoptosis in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the corresponding changes, ICAM1 was upregulated. ICAM1, which is a single-chain cell surface glycoprotein, is a molecule that has significant roles in the inflammatory response and in the recruitment of leukocytes to sites of inflammation ( 30 , 31 ). ICAM1 promotes adhesion at inflammatory sites and regulates the immune response, which is very beneficial in acute SCI.…”
Section: Discussionmentioning
confidence: 99%
“…SCs may promote BMSC differentiation into neuron-like cells and co-grafting these two types of cells can improve functional recovery after SCI via the PI3K-Akt signaling pathway. As mentioned above, “CAMs” and “leukocyte transendothelial migration” play crucial roles in regulating adhesion at inflammatory sites and in the immune response ( 30 , 31 ). It has been reported that PPAR activation can induce anti-inflammatory and antioxidant effects, provide vascular protection, and inhibit apoptosis in the nervous system; thus, PPAR may be a novel pharmacological target in neuroprotection ( 50 - 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The brain and spinal cord share a common origin, which is supported by the co-expression of specific neurotransmitters in both locations. Therefore, SCI and the abnormal discharge of brain neurons producing seizure might be closely related [14]. However, KA follows towards the lower parts and will cause rapid stiffness of the lower limbs and tail, producing paraplegia (paralysis of the lower extremities).…”
Section: Administration Of Kamentioning
confidence: 99%